Coordinated Control for Driving Mode Switching of Hybrid Electric Vehicles - Yanyan Zuo; Rui Sun; Jiuyu Zang; Mingyin Zheng (Shock and Vibration)
Taking a hybrid electric vehicle using double-row planetary gear power coupling mechanism as a research object, this study proposes a coordinated control algorithm of “torque distribution, engine torque monitoring, and motor torque compensation” in an attempt to realize coordinated control for driving mode switching. Characteristic analysis of the power coupling mechanism was carried out, and the control strategy model in MATLAB/Simulink was built. Subsequently, the analysis of mode switching from the electric mode into joint driving mode was simulated. In addition, a multibody dynamics model of the power coupling mechanism was established and the simulation analysis during mode switching process was carried out. The results show that the proposed coordinated control strategy serves to effectively reduce the torque fluctuation and the impact degree during the mode switching process and improve the ride comfort of the vehicle. In the meantime, the time-domain and frequency-domain characteristics of gear meshing force and bearing restraint force indicate that the mode switching process of the dynamic coupling mechanism is quite stable and this control strategy contributes to improving the characteristics such as vibration and noise.